COMPANY'S CSR ACTIVITIES ADDRESSED TO ITS CUSTOMERS - Grzegorczyk, Joanna Maria (Acta Universitatis Nicolai Copernici. Zarządzanie, 2020)
Entrepreneurs increasingly perceive the need to engage in corporate social responsibility activities, which in the long term bring many benefits, both for the company and its stakeholders. The article adopts the thesis that the key stakeholder of every enterprise is its clients. The purpose of this article is to indicate what corporate social responsibility is and to formulate CSR activities that entrepreneurs can take. Presented practices are addressed to customers - the most important stakeholders of enterprises.